2020
DOI: 10.1016/j.autneu.2019.102624
|View full text |Cite
|
Sign up to set email alerts
|

Activation of bradykinin-sensitive pericardial afferents increases systemic venous tone in conscious rats

Abstract: The venous system plays a critical role in blood pressure regulation by controlling venous return, cardiac filling, and cardiac output. Sympathetic drive is a major controller of venous function. However, outside of the arterial baroreflex, the mechanisms that regulate sympathetic drive to veins remain poorly defined in both physiological and disease conditions. The heart itself has an important sensory function via a variety of cardiac receptors that modulate cardiovascular function by neural and humoral refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…One possibility is that the dichotomous hemodynamic responses were dependent on the balance of afferent activation produced by pericardial BK injection. It is noteworthy that our approach, which mirrored that of McDermott ( McDermott et al, 1995 ) and our previous study ( Martin et al, 2020 ), used a pericardial catheter fixed in place along the lateral left ventricle to inject into the pericardial sac. Thus, the injectate was able to circulate within the pericardial sac and likely activated different types of cardiac afferents leading to overall activation of bradykinin-sensitive pericardial afferents.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…One possibility is that the dichotomous hemodynamic responses were dependent on the balance of afferent activation produced by pericardial BK injection. It is noteworthy that our approach, which mirrored that of McDermott ( McDermott et al, 1995 ) and our previous study ( Martin et al, 2020 ), used a pericardial catheter fixed in place along the lateral left ventricle to inject into the pericardial sac. Thus, the injectate was able to circulate within the pericardial sac and likely activated different types of cardiac afferents leading to overall activation of bradykinin-sensitive pericardial afferents.…”
Section: Discussionmentioning
confidence: 96%
“…This work in male rats using pressure-volume loop analysis indicated that localized epicardial BK application increased overall systemic flow, CO, by approximately 14% ( Wang et al, 2017 ). Since we reported previously that pericardial bradykinin injection increased venous tone ( Martin et al, 2020 ), we expected increased CO in response to pericardial bradykinin injection. In fact, we observed two distinct patterns of pericardial BK-induced hemodynamic responses.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Veins play an important role in the control of cardiovascular function by regulating venous return, cardiac output, and, therefore, arterial blood pressure. Our previous work showed that pericardial injection of bradykinin increased MCFP, an index of venous tone(Martin et al, 2020). We also reported that disinhibition of the PVN increased venous tone(Martin et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Institutionally supported core facilities performed comprehensive assessments of the impact of VTD on live animals. Both the Physiology Core Facility [ 50 53 ] and the Behavioral Core Facility [ 29 , 54 , 55 ] at the University of South Dakota have published in their respective specialties. Blood/tissues were collected, and subsequent bioanalysis was performed by collaborators at the Center for Human Toxicology at the University of Utah.…”
Section: Methodsmentioning
confidence: 99%